Perempuan dalam Film Religius: Ayat-ayat Cinta dan Perempuan Berkalung Sorban - Pangiuk, Ambok (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2010)
This articles aims to be a semiotics analysis towardsHanung Bramantyoâs movie Ayat-Ayat Cinta (AAC) and PerempuanBerkalung Sorban (PBS). This article starts from the fact that sincethis movie launched in 22 February 2008, AAC gained hugeattentions for audiences. Meanwhile, PBS gained negativeresponses by many criticisms toward this movie. Based on theanalysis, both movies have religious topics so that they consideredas religious movies, as the audiences identified them. Thus, onething that made these movies different was the portraying ofpolygamy in the movie. AAC focused on man as a polygamy actorwhich brought no issues arise. While PBS focused on woman as apolygamy victim that led to her suffer. However, AAC used manperspective that is called anti-feminist while PBS used womanperspective that is called as feminist movie.